2007
DOI: 10.1016/j.chembiol.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Control of Oxygenation in Lipoxygenase and Cyclooxygenase Catalysis

Abstract: Lipoxygenases (LOX) and cyclooxygenases (COX) react an achiral polyunsaturated fatty acid with oxygen to form a chiral peroxide product of high regio- and stereochemical purity. Both enzymes employ free radical chemistry reminiscent of hydrocarbon autoxidation but execute efficient control during catalysis to form a specific product over the multitude of isomers found in the nonenzymatic reaction. Exactly how both dioxygenases achieve this positional and stereo control is far from clear. We present four mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
284
0
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(303 citation statements)
references
References 106 publications
7
284
0
10
Order By: Relevance
“…This mechanistic difference of the first and second oxygenation allows exhibition of their different regioselectivity even though the normal on-site oxidation of hydroxyheme results in the same regioselectivity. Studies on COX and lipoxygenase have concluded that their regioselectivity for the radical addition of O 2 is controlled cooperatively by several factors including steric shielding and radical localization (31). Because the β-, γ-, and δ-meso heme carbons appear to be accessible (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanistic difference of the first and second oxygenation allows exhibition of their different regioselectivity even though the normal on-site oxidation of hydroxyheme results in the same regioselectivity. Studies on COX and lipoxygenase have concluded that their regioselectivity for the radical addition of O 2 is controlled cooperatively by several factors including steric shielding and radical localization (31). Because the β-, γ-, and δ-meso heme carbons appear to be accessible (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The serum-starved cells were then washed three times with DMEM, including 0.2% FBS, to remove the aspirin and then were serum-stimulated by incubation in DMEM, including 20% FBS, to induce muCOX-2 protein. After 3 h, the medium was removed and replaced with 2 ml of MEM containing 10% FBS and 10 nmol of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]arachidonic acid (ϳ300,000 cpm) and incubated for 10 min at room temperature. Subsequently, 1 N citric acid and 10% butylated hydroxytoluene were added to stop the reaction (21), and prostaglandins were extracted from cell suspension by adding 8 ml of hexane/ethyl acetate (1:1, v/v) and centrifuged to separate the phases for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The enzymes are commonly referred to as COX-1 and COX-2, and we use this latter terminology here. COXs catalyze the committed step in prostanoid biosynthesis, which is the conversion of one molecule of arachidonic acid, two O 2 molecules, and two electrons to prostaglandin endoperoxide H 2 (1)(2)(3)(4). PGH 2 is the immediate precursor of what are considered to be the major bioactive prostaglandins (PGs), including PGD 2 , PGE 2 , PGF 2␣ , PGI 2 , and thromboxane A 2 .…”
mentioning
confidence: 99%
“…The different members of the LOX superfamily, whether prokaryotic, plant, fungal, invertebrate, or vertebrate/mammalian, all retain the same conserved amino acids at the catalytic center and share a common structural framework (6 -12). Taken together with an in-depth understanding of the basic chemistry involved in LOX catalysis (4,(13)(14)(15), this similarity has led to models in which much of the diversity in product formation is accounted for by proposed differences in substrate binding ( Fig. 1) and by the direction of oxygen attack on the activated fatty acid.…”
Section: Lipoxygenases (Lox)mentioning
confidence: 99%
“…The diversity is such that individual LOX enzymes are known that can account for oxygenation on almost all the available positions on the common polyunsaturated fatty acid substrates (3)(4)(5). The different members of the LOX superfamily, whether prokaryotic, plant, fungal, invertebrate, or vertebrate/mammalian, all retain the same conserved amino acids at the catalytic center and share a common structural framework (6 -12).…”
Section: Lipoxygenases (Lox)mentioning
confidence: 99%